PENGARUH MOTIVASI KERJA DAN SUPERVISI KEPALA SEKOLAH TERHADAP MANAJEMEN PEMBELAJARAN GURU SMP NEGERI - Rospiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes teacher work motivation, principal supervision, and teacher learning management. It is aimed to examine and analyze the influence of teacher work motivation and principal supervision on the learning management of junior high school teachers. The study described in this article used a quantitative approach with a survey method. The population in the study involved 113 public junior high school teachers in Bagan Sinembah by using the Slovin formula. The sampling technique used the proportional random sampling technique. The data collection technique used a questionnaire with a Likert scale, analyzed by using correlation and regression techniques through the Microsoft Excel software program. The results of the study showed that there was a significant influence between Teacher Work Motivation and Teacher Learning Management which is proven the correctness. And then, there was a significant influence between Principal Supervision and Teacher Learning Management, which is proven the correctness. In addition, there was a significant influence between Teacher Work Motivation and Principal Supervision on Management Teacher learning, which is proven the correctness. Thus, the alternative hypothesis (Ha) was accepted, and the null hypothesis (H0) was rejected. Clearly, high teacher work motivation and good principal supervision influenced the teacher learning management better.